“Evaluación del impacto económico y asistencial de la pandemia COVID-19 en Centros y Consultorios Odontológicos de Trujillo-2020” - Villate Eusebio, Daniela (2022)
Evaluation of the Economic and Assistance Impact of the COVID-19 Pandemic in in Dental Centers and Offices of Trujillo-2020".Objective: To know the Economic and Assistance impact produced by the COVID-19 Pandemic in in Dental Centers and Offices in the city of Trujillo in 2020.Methodology: This research work is descriptive, cross-sectional and observational.Material and method: The sample consisted of a total of 177 Dental Surgeons, 103 females (58.19%) and 74 males (41.81%); of which 56 (31.64%) Dental Surgeons have a professional practice between 1-5 years, 79 (44.63%) between 6 to 10 years, 30 (16.94%) between 11 and 15 years and 12 (6.78%) more than 15 years. Likewise, 76 (42.94%) Dental Surgeons had a specialty and 101 (57.06%) had no specialty.Results: The Assistance Impact of the COVID-19 Pandemic in Dental Centers and Offices was negative, the degree of severity being predominantly "Mild" (68.4%) and "Moderate" with (27.7%), a significant statistical relationship of this variable was also determined when compare it with the "Professional Exercise Time" and the "Specialty". While the Economic Impact was negative, being predominantly of severity degree "Mild" (55.9%) and "Moderate" with (36.2%), a statistically significant relationship of this variable was also determined when compared with the "Specialty".Conclusions: Economic and Assistance Impact of the COVID-19 Pandemic in Dental Centers and Offices was predominantly negative, being mostly "Mild" and "Moderate" degree of severity for both cases.